2022
DOI: 10.1001/jama.2021.22482
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Maternal Hormonal Contraception Use and Central Nervous System Tumors in Children

Abstract: IMPORTANCEThe incidence of central nervous system (CNS) tumors in children appears to be increasing, yet few risk factors are established. There is limited information regarding whether maternal hormonal contraception use increases this risk.OBJECTIVE To examine the association between maternal hormonal contraception use and CNS tumors in children (<20 years). DESIGN, SETTING, AND PARTICIPANTSIn this nationwide cohort study based on population-based registry data, 1 185 063 children born in Denmark between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A cohort study in JAMA provides further evidence that use of maternal hormonal contraceptives does not explain a rise in the incidence of CNS tumours in children since the 1970s. This large, prospective, population based study found no association between the two 5. It included all live-born children born in Denmark between 1995 and 2014—a total of 1 185 063 children—thereby winning this week’s prize for best population coverage in a research paper.…”
Section: Article Of No Associationmentioning
confidence: 99%
“…A cohort study in JAMA provides further evidence that use of maternal hormonal contraceptives does not explain a rise in the incidence of CNS tumours in children since the 1970s. This large, prospective, population based study found no association between the two 5. It included all live-born children born in Denmark between 1995 and 2014—a total of 1 185 063 children—thereby winning this week’s prize for best population coverage in a research paper.…”
Section: Article Of No Associationmentioning
confidence: 99%
“…The report by Hargreave et al in this issue of JAMA demonstrated that most hormonal contraceptives used by the vast majority of women are not associated with CNS tumors in offspring. The isolated finding of a possible higher risk associated with progestin-only injections was based on very small numbers of cases, whereas no other progestin-only contraceptives, which may be expected to act similarly on cancer risk, showed an association with CNS tumors.…”
mentioning
confidence: 98%
“…In this issue of JAMA , Hargreave et al examined the association between maternal hormonal contraception use and CNS tumors in their offspring. The authors used data from a population-based registry from Denmark and included 1185 063 children born between 1996 and 2014.…”
mentioning
confidence: 99%
See 2 more Smart Citations